The Effect of Return on Assets Ratio, Debt to Equity Ratio and Sales Growth on Tax Avoidance (Jurnal Manajemen Bisnis, 2024)
This study aims to determine the role of Return On Assets Ratio (ROA), Debt To Equity Ratio (DER), and Sales Growth on Tax Avoidance, with a research focus on the Energy sector listed on the Indonesia Stock Exchange for the 2020-2022 period. A sample of 45 companies was used, taken using the purposive sampling technique. The data analysis technique used is quantitative analysis. This analysis shows that ROA and DER have a significant effect on Tax Avoidance, while sales growth has no effect. The data management procedure was carried out with the help of IBM SPSS 26.